Menumbuhkan Sikap Sosial melalui Pembelajaran IPS pada Peserta Didik SD Home Schooling Primagama Banjarmasin - Huriyah Huriyah (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Abstract This study aims to foster social attitudes through social studies learning in students at Banjarmasin Primagama Home Schooling. The researcher used qualitative research method. Data collection techniques were field observations, interviews, documentation, and triangulation. Data analysis in this study used an interactive model analysis, namely data reduction, data presentation, and conclusion. Based on the results of the study, it can be seen (1) that social studies learning at  Banjarmasin Primagama  Home Schooling can foster students' social attitudes by teaching instructors to provide social studies based on relevant, systematic, and infrastructure resources in accordance with the learning and community environment. (2) that instructors and psychologists evaluate the learning outcomes and the development of students' behavior so that they can foster social attitudes of students with a home schooling system.